Catastrophic antiphospholipid syndrome presenting with aortic barrage: case report and review of the literature. (May 2021) - Moroni, Luca; Righini, Paolo; Ramirez, Giuseppe A; Farina, Nicola; Mancuso, Gaia; Bozzolo, Enrica; Rodríguez-Pintó, Ignasi; Cervera, Ricard; Nano, Giovanni; Dagna, Lorenzo
Catastrophic antiphospholipid syndrome (CAPS) is a life-threatening condition characterized by multiple thromboembolic events occurring in a short period of time, frequently accompanied by significant systemic inflammation. Aortic involvement is rare in antiphospholipid syndrome and it had been never described in the context of its catastrophic variant. Here, we report an unusual case of aortic occlusion as a debut manifestation of CAPS and discuss its clinical features with an up-to-date review of the literature to identify risk factors and clues for clinical practice.